THE URGENCY OF BELIEVING THE LAST VERSES OF SYAIKH NAJMUDDIN AL-KUBRA'S PERSPECTIVE (A STUDY OF THE INTERPRETATION OF TASAWUF AKHLAQI) - Badrudin; Salim Rosyadi; Rizal Ahmad Fauzi (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
The eschatological phenomenon which states that life in the world will end when death comes, so that those who experience death will be delivered to the afterlife, this becomes a theological basis for Muslims to be implied in their lives in the world, because the afterlife along with its fate or journey is a reflection of oneself in living life in the world. Examining the verses of the Qur'an that discuss the afterlife has relevance to the interpretation of Shaykh Najmuddin al-Kubra in the book of tafsīr at-ta'wīlāt an-najmiyyah which has a style of isyari or sufistic interpretation, so that understanding the verses about the afterlife becomes new knowledge that is applied and experienced using the heart. This research produces a discussion of the verses of the Qur'an that explain the afterlife, such as the explanation of the realm of barzakh (QSal-Mu'minun: 100), the Day of Judgment (QSibrahīm: 48), the realm of resurrection (QSar-Rūm: 56), Yaum al-Mīzān (QSal-A ʻraf : 8-9), Yaum al- Ḥisāb (QSal-Kahf: 49), Yaum at-Tagābun (QSat-Tagābun: 9), Yaum al-Aʻraf (QSal-Aʻraf: 46), hell (QSal-Baqarah: 24), and heaven (QSaz-Zumar: 73). Thus, this research concludes that the fate of a creature will be determined according to the good deeds carried during life in this world. If more good deeds are brought then the fate of life in the afterlife will be determined by Allah SWT, but conversely if there are more bad deeds brought then the fate of life in the afterlife will be a place cursed by Allah SWT.